2014
DOI: 10.1007/s00394-014-0809-6
|View full text |Cite|
|
Sign up to set email alerts
|

Maternal vitamin C deficiency during pregnancy results in transient fetal and placental growth retardation in guinea pigs

Abstract: Although no clinical differences between CTRL and DEF pups were observed at GD56, the present data suggest that vitC plays a role in early fetal development. Although no clinical differences between CTRL and DEF pups were observed at GD56, the present data suggest that vitC plays a role in early fetal development. Low maternal vitC intake during pregnancy may compromise maternal weight gain, placental function and intrauterine development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 83 publications
1
21
0
2
Order By: Relevance
“…Thus in this study—in spite of the fetus acting as a “parasite” as described by Teel et al [3]—the newborns of mothers with low maternal vitC seem not to be able to obtain the same level of vitC in the umbilical cord as newborns of mothers with a higher vitC level, although their ratio is larger. This is in line with experimental data from guinea pigs showing that the preferential fetal transport may be overridden by increased needs of the mother during situations of deficiency, thereby potentially influencing the health of the offspring [13,49]. In accordance, the vitC levels of the umbilical cord blood correlated positively with the obtained Apgar score of the newborn.…”
Section: Discussionsupporting
confidence: 87%
“…Thus in this study—in spite of the fetus acting as a “parasite” as described by Teel et al [3]—the newborns of mothers with low maternal vitC seem not to be able to obtain the same level of vitC in the umbilical cord as newborns of mothers with a higher vitC level, although their ratio is larger. This is in line with experimental data from guinea pigs showing that the preferential fetal transport may be overridden by increased needs of the mother during situations of deficiency, thereby potentially influencing the health of the offspring [13,49]. In accordance, the vitC levels of the umbilical cord blood correlated positively with the obtained Apgar score of the newborn.…”
Section: Discussionsupporting
confidence: 87%
“…Vitamin C is an antioxidant which contributes to cellular antioxidant defense (Preston, 1991;Tous et al, 2019). A study in pigs found that vitamin C deficiency during pregnancy could cause brain damage in the offspring (Schjoldager et al, 2015). Giving smoking women vitamin C during pregnancy was shown to improve lung function (better airflow and less wheezing) in children during the first year of life (McEvoy et al, 2014).…”
Section: The Role Of Oxidative Stress In the Development Of Asthma Inmentioning
confidence: 99%
“…Maternal ascorbate deficiency in guinea pigs (which have no endogenous production of ascorbate) during pregnancy resulted in lower fetal levels of plasma ascorbate, and reduced fetal body weight and brain weight [123]. Insufficient ascorbic acid intake during the gestation of Gulo − / − mice (also have no endogenous ascorbate production) resulted in neonatal lethality [71].…”
Section: Epigenetic Regulation Of Ascorbate In Embryonic Developmentmentioning
confidence: 99%